Efektivitas Terapi Latihan Pada Pasien Post-Op Rekontruksi Acl : Literatur Review - Arip Maulana Yahya; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2026)
ACL reconstruction is a common surgery done to restore knee stability, but many patients still experience pain, muscle weakness, and reduced function after the operation. Exercise therapy is a key part of rehabilitation after ACL reconstruction. This review looked at ten randomized controlled trials (RCTs) that evaluated different types of exercises, including neuromuscular training, progressive resistance exercise, visuo-motor training, aquatic proprioceptive exercise, and blood flow restriction training, during the middle to later stages of rehabilitation. Each study had an intervention period of 6 to 20 weeks, and used tools like KOOS, IKDC, SF-36, and Hop Test to measure results. The analysis showed that all types of exercise significantly improved muscle strength, balance, proprioception, and knee function, while also reducing pain and fear of movement. Neuromuscular and progressive resistance exercises were found to be the most effective in improving muscle symmetry and functional performance. Evidence-based exercise approaches, patient education, and the use of digital tools (mHealth) and hydrotherapy also helped increase patient adherence and quality of life. Therefore, structured, progressive, and multimodal exercise programs are recommended as the main strategy in ACL reconstruction rehabilitation to speed up recovery and prevent future injuries.